Regularities of La distribution in humic psammozem profile of Transbaikalia and soil-root layer microzones of maize during the vegetation period - Afanasyeva, Larisa; Kozhevnikova, Nina (International Journal of Environment, 2014)
In Transbaikalia information about accumulation, distribution of rare earth elements (REEs) in soils, their transportation from soil to plants is very rare. The aim of this study was to assess the migration of lanthanum in a soil profile and soil-root layer microzones of maize during the vegetation period. The study is based on a field approach in non-polluted natural sites. Concentration of total content La and its mobile form (acid-soluble, exchangeable and water-soluble) in the soil and soil root layer of maize was determined using method of selective extraction Gobran and Glegg. Maximum concentration total La was founded in the upper part of the soil (0 to 15 cm depth). The content of the La mobile forms is 6.9-11.2% from the total amount. The distribution of the element mobile forms within the profile is relatively even. Results indicated that concentration La mobile forms changed in accordance with the phase of maize development. The higher concentration of mobile forms (17-120% from germination period) was founded in soil-root layer microzones in the blossom period. DOI: http://dx.doi.org/10.3126/ije.v3i2.10527 International Journal of the Environment Vol.3(2) 2014: 213-220